2024
DOI: 10.3389/fphys.2024.1338507
|View full text |Cite
|
Sign up to set email alerts
|

Making the case for resistance training in improving vascular function and skeletal muscle capillarization

Mason C. McIntosh,
Derick A. Anglin,
Austin T. Robinson
et al.

Abstract: Through decades of empirical data, it has become evident that resistance training (RT) can improve strength/power and skeletal muscle hypertrophy. Yet, until recently, vascular outcomes have historically been underemphasized in RT studies, which is underscored by several exercise-related reviews supporting the benefits of endurance training on vascular measures. Several lines of evidence suggest large artery diameter and blood flow velocity increase after a single bout of resistance exercise, and these events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 120 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…Exercise has profound effects on the human vascular system ( 1-3 ). McIntosh et al ( 4 ) reported that the effect of exercise on the diameter and blood flow of arteries within skeletal muscles has been significantly underestimated in the past, only receiving attention recently. There is evidence to suggest that even single sessions of moderate-intensity exercise can increase blood flow velocity within arteries and affect their diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise has profound effects on the human vascular system ( 1-3 ). McIntosh et al ( 4 ) reported that the effect of exercise on the diameter and blood flow of arteries within skeletal muscles has been significantly underestimated in the past, only receiving attention recently. There is evidence to suggest that even single sessions of moderate-intensity exercise can increase blood flow velocity within arteries and affect their diameter.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of exercise on the diameter of blood vessels and blood flow within skeletal muscles are profound ( 1-3 ); however, it has only recently garnered sufficient attention in the medical community ( 4 ). Wearing myopia glasses is a common method to correct myopia.…”
Section: Introductionmentioning
confidence: 99%